2022
DOI: 10.1021/acs.jmedchem.2c00988
|View full text |Cite
|
Sign up to set email alerts
|

Novel Efficient Multistage Lead Optimization Pipeline Experimentally Validated for DYRK1B Selective Inhibitors

Abstract: In addition to general challenges in drug discovery such as the identification of lead compounds in time- and cost-effective ways, specific challenges also exist. Particularly, it is necessary to develop pharmacological inhibitors that effectively discriminate between closely related molecular targets. DYRK1B kinase is considered a valuable target for cancer-specific mono- or combination chemotherapy; however, the inhibition of its closely related DYRK1A kinase is not beneficial. Existing inhibitors target bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Alexandrov and colleagues have recently reported an inventive pipeline for optimization of DYRK1B selective inhibitors (Alexandrov et al, 2022). However, the major obstacle for this and other structure based design methods was that experimental structure of DYRK1B was not available.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Alexandrov and colleagues have recently reported an inventive pipeline for optimization of DYRK1B selective inhibitors (Alexandrov et al, 2022). However, the major obstacle for this and other structure based design methods was that experimental structure of DYRK1B was not available.…”
Section: Resultsmentioning
confidence: 99%
“…Alexandrov et al ( 7 ) reported a pipeline for optimizing selective inhibitors for DYRK1B. However, the key challenge in this and other structure-based design approaches was the lack of the experimental structure for DYRK1B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations